KINERJA PEMERINTAH KECAMATAN TOBELO UTARA KABUPATEN HALMAHERA UTARA - ALDRIN, HABARI ALDRIN (JURNAL ADMINISTRASI PUBLIK, 2013)
Aldrin Habari Thesis titled "Government Performance Sub North Tobelo North Halmahera as one of the requirements for a bachelor's degree at the Faculty of Social and Political Science, University of Sam Ratulangi in Manado Guided by Drs.W.Y.Rompas, Msi and Dra.Joyce.J.Rares ,MsiResearch in the framework of the preparation of Tier One Degree thesis at the Faculty of Social and Political Sciences Unsrat was preceded by preliminary observations that the results show that the performance of the government district of North Tobelo North Halmahera indicated low. Thus, this study aims to assess the performance of the District Government organization North Tobelo North Halmahera. This study uses an approach or descriptive-qualitative method. Data were collected through interview techniques, observation and questionnaires were distributed to 42 respondents coming from the government district, village government and community service users in North Tobelo District Office. Once the data is collected, then analyzed by applying the frequency table analysis (analysis of the percentage). The results showed that the performance of the government district of North Tobelo, which consists of six dimensions, namely productivity, quality of service, responsiveness (responsiveness), responsibility, public accountability and justice, it is the lowest dimension of justice, while the highest average achievements is the dimension of public accountability. The low average achievement of justice has to do with cultural values are still strong paternalistic society, where officials and people were still able to be treated special than ordinary people.The conclusion that can be drawn from these results is that in general, the achievement of the performance of the District Government of North Tobelo quite high, but not optimally. This is because this new district was expanded about six years ago (still life of a baby), so there are still many limitations, both in terms of power sumebr apparatus, facilities / infrastructure, equipment and facilities of public pelaynan. It is recommended that the government should run a program empowering and coaching personnel through the establishment and coordination of Board meetings pengefektivan Harmony Ummah (bku).Keywords: Performance, Government, District.